X-RAY DIAGNOSTICS OF DISEASES OF THE PANCREATIC GLAND - Dorofeeva, Tamara; Rozhkovska, Galina; Tsvigovskiy, Viatcheslav; Dolgushyn, Oleg; Korsun, Oleksandr; Krupnyk, Inna; Dius, Olena; Slyusarenko, Olesya; Sokolov, Viktor (European Science, 2023)
The article considers the problems of acute and chronic pancreatitis, as well as pancreatic tumors